Development of a nursing website for critical care regarding healthcare-associated infections - Eliézer Farias de Mello; Bárbara Alessandra Tibério; Mitzy Tannia Reichembach; Letícia Pontes
ABSTRACT Objective: to describe the development of a website about the main healthcare-associated infections and the respective bundles to prevent these diseases, oriented toward intensive care unit nursing. Methods: experience report describing the development of technological innovation by nurses, using computational tools and technological production methodological research and following the product development process. Results: nurses developed an educational website which can be accessed through computers, tablets, and smartphones at the electronic address irastis.com and focuses on healthcare-associated infections. Final considerations: digital technologies have contributed to fulfill demands in health care, research, and education. The developed website has the potential to support reduction in healthcare-associated infection rates, since it makes preventive measures for these infections available and refers users to publication environments that systematize the implementation of the bundles.